First detection of rotavirus group C in asymptomatic pigs of smallholder farms in East Africa - Amimo, Joshua O.; Machuka, Eunice M.; Okoth, Edward A. (MDPI, 2017)
Abstract: Group C rotavirus (RVC) has been described to be a causative agent of gastroenteritis in humans and animals including pigs, cows, and dogs. Fecal samples collected from asymptomatic pigs in smallholder swine farms in Kenya and Uganda were screened for the presence of group C rotaviruses (RVC) using a reverse transcription-polymerase chain reaction assay. A total of 446 samples were tested and 37 were positive (8.3%). A significantly larger (p < 0.05) number of RVC-positive samples was detected in groups of older pigs (5–6 months) than in younger piglets (1–2 months). There were no significant differences in the RVC detection rate between the pigs that were full time housed/tethered and those that were free range combined with housing/tethering. After compiling these data with diagnostic results for group A rotaviruses (RVA), 13 RVC-positive samples were also positive for RVA. This study provides the first evidence that porcine group C rotavirus may be detected frequently in asymptomatic piglets (aged < 1–6 months) in East Africa. The occurrence of RVC in mixed infections with RVA and other enteric pathogens requires further research to investigate the pathogenic potential of RVC in pigs.